Pengaruh Pemberian Pakan pada Pembesaran Ikan Nila (Oreochromis niloticus) di Balai Benih Ikan Teun - Moruk, Adelbertus Ronaldo; Liubana, Debora Victoria (Jurnal Akuakultur Sungai dan Danau, 2025)
Nile tilapia (Oreochromis niloticus) is one of the high-value aquaculture commodities, with steadily increasing demand for both seed and consumption purposes. However, the development of tilapia farming in Indonesia still faces challenges, particularly in terms of the availability and quality of seed. As a freshwater fish with a fast growth rate and high adaptability, tilapia has strong potential to be cultivated intensively. The grow-out of Nile tilapia requires attention to key factors such as water quality management, availability of aquaculture land, and the implementation of environmentally friendly technologies. With an efficient cultivation system and proper management, tilapia farming can serve as a strategic solution to increase freshwater fish production to meet market demand. The development plan for tilapia grow-out farming by BBI Teun is a concrete step in supporting food security and fostering growth in the national fisheries sector